Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
The equation to use is
y = mx + c
The first thing you need to know is the gradient represented by the m
Do you know how to find the gradient
y = mx + c
The first thing you need to know is the gradient represented by the m
Do you know how to find the gradient
Answer:
y = -3x² - 3x + 6
Step-by-step explanation:
main formula: r×(x² - (a + b)x + ab) = y
r×(x² - (-2 + 1)x -2×1) =y
r×(x² +x -2) = y
by using the point (0,6) →
r×(0² + 0 -2) = 6
r×-2 = 6
r= -3
so
y= -3x² -3x +6
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.